The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s12939-021-01379-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of health insurance on poverty among rural older adults: an evidence from nine counties of western China

Abstract: Background Older adults are more prone to various diseases. Health insurance becomes effective mechanism to relieve financial burden when the insured is sick. In China, most older adults live in the countryside, and New Rural Cooperative Medical Scheme is a kind of health insurance system in rural areas. The relationship between New Rural Cooperative Medical Scheme and financial burden due to health expenditure of older adults in China was investigated. This paper aims at the impact of New Rura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…The CBHI has decreased household per-capita health expenditure of the insured group by 17, 15, and 14 percentage points for nearest-neighbor, Kernel-based, and radius matching, respectively. This finding is similar to other studies ( 2 , 14 , 47 , 48 ).…”
Section: Resultssupporting
confidence: 93%
“…The CBHI has decreased household per-capita health expenditure of the insured group by 17, 15, and 14 percentage points for nearest-neighbor, Kernel-based, and radius matching, respectively. This finding is similar to other studies ( 2 , 14 , 47 , 48 ).…”
Section: Resultssupporting
confidence: 93%
“…Similarly in China it was found that in 2008 about 15% of older adults consumed at levels below the World Bank's $1.25/day international poverty line [54]. Another study in China revealed that about 33% of older adults were identified as falling in poverty [55]. The present study found that the self-perceived income status is more associated with mental health conditions than any other single indicator of SES.…”
Section: Discussionsupporting
confidence: 48%
“…It also demonstrates that poor health and poverty work through multiple pathways, providing a guide on how to break the health–poverty cycle. Moreover, the level of health varies from province to province [ 48 , 49 ]. Therefore, while each has its own focus, improving individual health and system health should be performed simultaneously to alleviate rural poverty effectively.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the limited role played by social medical insurance may be another explanation. China proposed the New Rural Cooperative Medical Scheme (NRCMS) in 2003 to make health care more affordable for the rural population, but scholars are divided on the program’s effectiveness [ 49 ]. Although there is government and social financial support, the NRCMS only covers a small part of rural patients’ medical expenses [ 62 , 63 , 64 ], and they still have to pay a large proportion of out-of-pocket expenses.…”
Section: Discussionmentioning
confidence: 99%